Measuring the Immeasurable: The Evolution of the Size of Informal Economy in the Agricultural Sector in the EU-15 up to 2019 - Friedrich Schneider; Mangirdas Morkunas; Erika Quendler (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This study is the first scientific attempt to calculate the size of the informal economy in agriculture. The Multiple indicators multiple causes model (MIMIC) was developed for the estimation of levels of informal economy in 15 “Old” European Union Member States' agricultural sectors for the period of 1996-2019. The obtained results document the prevalence of higher levels of informal economy in agriculture compared to the overall economy. The impact of subsidies and farm organizations on the development of the informal economy are two important factors for these higher values in agriculture. The effects of taxation, share of import and factor income in agriculture onto the levels of the informal economy in agriculture are sizeable, too. Finally, we disaggregate the informal work into subcategories like entrepreneurial and family work.
Keywords: Q11; Q14; Q19; 330; informal economy; informal work; agriculture; MIMIC; EU-15 countries; causes for informal work